Posted by **James** on Tuesday, May 22, 2007 at 1:08am.

2(3x - 7) + 4 (3 x + 2) = 6 (5 x + 9 ) + 3

how will solve it?

well you first multiply it out:

6x-14+12x+8=30x+54+3

you combine like terms

18x-6=30x+57

-12x=63

x=-63/12

## Answer this Question

## Related Questions

- math, algebra - can someone correct this for me or help me. 6x^2y^3+ 9x^2y^3 ...
- Algebra: factoring - I need to find the value of x. 9x^3 + 9x = 30x^2 It's ...
- Math - The problem to solve is: (x+20)(x-12)(x+4)>0 but I can't figure out ...
- Algebra - Can someone please help solve this? Solve by using addition or ...
- Algebra II - Solve 1. 3x^2-9x=0 2. 12x^2+30x=-12 3. 9a(a+1)=4 4. 16x^2=25
- Maths - you have to solve the following by finding the value of x and y. can u ...
- Algebra - Convert the simplified parabolic equation y=3x^2-30x-7 to standard ...
- algebra - factor out the greatest common factor from the expression 18x^5+48x^2-...
- Algebra - I need help trying to put the correct vocabulary words when solving ...
- ALGEBRA - If I divide 28x^3-30x^2-67x-21 BY 7x+3...will I get 4x^2-10x-21? THEN ...